Family business success : the role of founder/CEO competence, family culture, organisation structure and successor development - Gan, Fong Jek (2009)
In Singapore, little is known about the characteristics and dynamics of family businesses. Other than occasional media coverage on family businesses in dispute and turmoil, nothing is written on the critical factors necessary for family business success. In an attempt to identify the factors associated with family business growth and profitability, this study developed a performance model for Singapore family business and empirically tested it. In specific, it examines the influence of